2019
DOI: 10.1177/0899764019830243
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurial Passion and Social Innovation Performance

Abstract: We develop a framework to explain the underlying processes by which social entrepreneurial passion affects social innovation performance. The findings from a survey of 229 U.K.-registered Community Interest Companies indicate that social entrepreneurial passion can positively influence social innovation performance through creative solution generation capacity (CSGC). We also distinguish the moderating effects of different interorganizational network connections on the relationship between social entrepreneuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 72 publications
1
42
0
Order By: Relevance
“…They found that entrepreneurial passion for inventing was strongly related to innovation, and that such a relationship was stronger when there were higher levels of distributive justice in the franchise relationship. Ko, Liu, Yusoff, and Mat (2019) found a strong link between the entrepreneurial passion of social entrepreneurs towards different activities and social innovation performance, and that this link was partly explained by the mediating mechanism of creative solution generation capacity. Finally, both Ma et al (2018) and Kiani, Ali, Kanwal, and Wang (2019) found that entrepreneurial passion for different activities was positively related to organizational innovation, and that such a relationship was stronger when entrepreneurs exhibited higher levels of Zhongyong thinking (a style of thinking which emphasizes interpersonal harmony and connection).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that entrepreneurial passion for inventing was strongly related to innovation, and that such a relationship was stronger when there were higher levels of distributive justice in the franchise relationship. Ko, Liu, Yusoff, and Mat (2019) found a strong link between the entrepreneurial passion of social entrepreneurs towards different activities and social innovation performance, and that this link was partly explained by the mediating mechanism of creative solution generation capacity. Finally, both Ma et al (2018) and Kiani, Ali, Kanwal, and Wang (2019) found that entrepreneurial passion for different activities was positively related to organizational innovation, and that such a relationship was stronger when entrepreneurs exhibited higher levels of Zhongyong thinking (a style of thinking which emphasizes interpersonal harmony and connection).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proper advertising placement, initial selection, connecting to the labour services and agencies all these require significant labour and financial costs. We suggest automating the customer relationship management stage (Ko, 2019;Belyakova, 2020;Pogosyan, 2018;Rahman, 2017).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Finally, it has also been observed that passion is an important element in predicting both service quality and sporting performance. The role of passion has not been widely studied in the sport sector in terms of sports clubs' performance, but there are examples where it has been analysed at the organisational level [80][81][82] as well as in the sports environment [56,83]. According to Baum and Locke [30], it is an important element that is associated with positive organisational results.…”
Section: Discussionmentioning
confidence: 99%